Awareness of deficits in Alzheimer's disease patients: Analysis of performance prediction discrepancies. Issue 4 (20th May 2013) - Antoine, Pascal; Nandrino, Jean‐Louis; Billiet, Caroline
<x xml:space="preserve">Abstract</x> Aim Unawareness has been operationalized in terms of a discrepancy between the patient's self‐reports and three main categories of standards: judgment of a relative, clinical assessment, and objective test performance. The purpose of this study was to develop a new measure of deficit unawareness based on multidimensional, isomorphic, simple tasks and to examine the relationship between this measure and neuropsychological tests. Methods Analysis was conducted on cognitive performance prediction discrepancies in a sample of Alzheimer's disease (AD) patients and a matched comparison group. Results Patients rated their cognitive functioning more highly than their performance, but their overall self‐reports were lower than the overall self‐reports of the comparison group. AD patients performed significantly lower than their predicted scores in all Dementia Rating Scale (DRS) domains, in contrast to comparison participants, who did not consistently perform significantly lower across domains. All unawareness scores were moderately inter‐correlated, except for memory, and all unawareness scores with the exception of memory were correlated with overall neuropsychological functioning. Conclusion A methodological and conceptual difficulty has been identified, and this raises the issue of the generalizability of studies with a focus on memory unawareness. The method proposed seems a good tool to assess the relationships between unawareness and several different aspects of cognitive functioning, in particular executive functioning.